2008
DOI: 10.1371/journal.pone.0002083
|View full text |Cite
|
Sign up to set email alerts
|

The Endosymbiont Wolbachia pipientis Induces the Expression of Host Antioxidant Proteins in an Aedes albopictus Cell Line

Abstract: Wolbachia are obligate intracellular bacteria which commonly infect arthropods. They are maternally inherited and capable of altering host development, sex determination, and reproduction. Reproductive manipulations include feminization, male-killing, parthenogenesis, and cytoplasmic incompatibility. The mechanism by which Wolbachia avoid destruction by the host immune response is unknown. Generation of antimicrobial peptides (AMPs) and reactive oxygen species (ROS) by the host are among the first lines of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 78 publications
6
119
0
2
Order By: Relevance
“…We note that in plantmicroorganism interactions, oxidative stress commonly occurs, for example, in rhizobial symbiosis (56) and also in phytopathogenic infections (35). More generally, it could be a common and fundamental mechanism occurring widely in many prokaryote-eukaryote interactions, as it has been described recently in the Aedes albopictus-Wolbachia symbiosis (11).…”
Section: Discussionmentioning
confidence: 67%
“…We note that in plantmicroorganism interactions, oxidative stress commonly occurs, for example, in rhizobial symbiosis (56) and also in phytopathogenic infections (35). More generally, it could be a common and fundamental mechanism occurring widely in many prokaryote-eukaryote interactions, as it has been described recently in the Aedes albopictus-Wolbachia symbiosis (11).…”
Section: Discussionmentioning
confidence: 67%
“…The maternally transmitted intracellular bacteria Wolbachia pipientis, which can reach a high prevalence in host populations as a result of reproductive manipulations-even when they are physiologically costly- [57], are interesting model systems to understand the maintenance of symbiosis through the evolution of tolerance mechanisms. In cultured cells from the mosquito Aedes albopictus, the infection by Wolbachia is associated with a higher level of ROS (H 2 O 2 ) and the synthesis of anti-oxidant proteins [58]. The artificial infection of Wolbachia in Ae.…”
Section: (C) Evolution Of Tolerance In Wolbachia-insect Symbiosesmentioning
confidence: 99%
“…Recent studies on diverse insect-microbe symbiotic associations have revealed that the host organisms regulate infection densities of their symbionts by means of phagocytosis, antimicrobial peptides, lysozymes, reactive oxygen species, etc. (39)(40)(41)(42). These innate immune mechanisms may also comprise host-related stress factors for the symbionts.…”
Section: Host Fitness Is Negatively Affected By Infection With Symbiontmentioning
confidence: 99%